Copper‐Catalyzed N‐ and O‐Arylation of Amides: Alternative Approaches to 3, 4‐Dihydroquinolin‐2‐ones, Quinolin‐2‐ones, and 12H‐Chromeno[2, 3‐b]quinolin‐12‐ones. Issue 36 (19th November 2013) - Zhang, Xinying; Guo, Xiaojie; Fang, Liangliang; Song, Yunping; Fan, Xuesen
Abstract: The efficient syntheses of 3‐cyanoquinolin‐2‐ones, 3‐(2‐bromobenzyl)‐3‐cyano‐3, 4‐dihydroquinolin‐2‐ones, 3‐(2‐bromobenzyl)quinolin‐2‐ones, and 12 H ‐chromeno[2, 3‐ b ]quinolin‐12‐ones through copper‐catalyzed N ‐ and O ‐arylation of amides by using readily available 2‐bromobenzyl bromides and cyanoacetamides as starting materials were developed. Abstract : New synthetic approaches to 3‐cyanoquinolin‐2‐ones (1 ), 3, 4‐dihydroquinolin‐2‐ones (2 ), 3‐(2‐bromobenzyl)quinolin‐2‐ones (3 ), and 12 H ‐chromeno[2, 3‐ b ]quinolin‐12‐ones (4 ) through copper‐catalyzed N ‐ and O ‐arylation of amides starting from 2‐bromobenzyl bromides (5 ) and cyanoacetamides (6 ) are developed.